Comparison of diffusion tractography and tract‐tracing measures of connectivity strength in rhesus macaque connectome - van den Heuvel, Martijn P. (Hum Brain Mapp, 2015)
With the mapping of macroscale connectomes by means of in vivo diffusion‐weighted MR Imaging (DWI) rapidly gaining in popularity, one of the necessary steps is the examination of metrics of connectivity strength derived from these reconstructions. In the field of human macroconnectomics the number of reconstructed fiber streamlines (NOS) is more and more used as a metric of cortico‐cortical interareal connectivity strength, but the link between DWI NOS and in vivo animal tract‐tracing measurements of anatomical connectivity strength remains poorly understood. In this technical report, we communicate on a comparison between DWI derived metrics and tract‐tracing metrics of projection strength. Tract‐tracing information on projection strength of interareal pathways was extracted from two commonly used macaque connectome datasets, including (1) the CoCoMac database of collated tract‐tracing experiments of the macaque brain and (2) the high‐resolution tract‐tracing dataset of Markov and Kennedy and coworkers. NOS and density of reconstructed fiber pathways derived from DWI data acquired across 10 rhesus macaques was found to positively correlate to tract‐tracing based measurements of connectivity strength across both the CoCoMac and Markov dataset (both P < 0.001), suggesting DWI NOS to form a valid method of assessment of the projection strength of white matter pathways. Our findings provide confidence of in vivo DWI connectome reconstructions to represent fairly realistic estimates of the wiring strength of white matter projections. Our cross‐modal comparison supports the notion of in vivo DWI to be a valid methodology for robust description and interpretation of brain wiring. Hum Brain Mapp 36:3064–3075, 2015. © 2015 Wiley Periodicals, Inc.